2020
DOI: 10.1016/j.ebiom.2020.102704
|View full text |Cite
|
Sign up to set email alerts
|

TH1579, MTH1 inhibitor, delays tumour growth and inhibits metastases development in osteosarcoma model

Abstract: Background: Osteosarcoma (OS) is the most common primary malignant bone tumour. Unfortunately, no new treatments are approved and over the last 30 years the survival rate remains only 30% at 5 years for poor responders justifying an urgent need of new therapies. The Mutt homolog 1 (MTH1) enzyme prevents incorporation of oxidized nucleotides into DNA and recently developed MTH1 inhibitors may offer therapeutic potential as MTH1 is overexpressed in various cancers. Methods: The aim of this study was to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…2 ). This explanation is logically more consistent than the idea that extant and unprocessed genomic 8-oxo-dG is the source of MTH1 inhibition-induced cytotoxicity, as has been previously suggested [ [9] , [10] , [11] , [12] ]. Our findings point to robust OGG1, and more generally robust BER activity, as an important determinant for tumor suppression arising from MTH1 inhibition.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…2 ). This explanation is logically more consistent than the idea that extant and unprocessed genomic 8-oxo-dG is the source of MTH1 inhibition-induced cytotoxicity, as has been previously suggested [ [9] , [10] , [11] , [12] ]. Our findings point to robust OGG1, and more generally robust BER activity, as an important determinant for tumor suppression arising from MTH1 inhibition.…”
Section: Discussionsupporting
confidence: 86%
“…The first-in-class MTH1 inhibitors, TH588 and TH287, have been shown to also produce DNA double strand break (53BP1) foci [ 8 ]. However in subsequent studies, the cytotoxicity of these inhibitors as well as their best-in-class derivative, TH1579 (karonudib) [ 9 ], has been attributed to their enhanced genomic 8-oxo-dG incorporation [ [9] , [10] , [11] , [12] ], as significant enhancement of DNA breaks relative to control conditions are observed only if recombinant OGG1 is added to the treated cells during the comet assay. However, a body of in vitro and in vivo work has shown that genomic 8-oxo-dG, in and of itself, is not a genotoxic lesion but instead a mildly mutagenic one [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NUDT family of enzymes is an intriguing family of enzymes that play a key role in the progression of breast and other cancers. The therapeutic potential of NUDT-selective inhibitors has already been shown—NUDT1-selective inhibitors have shown efficacy in multiple studies in vitro and in vivo [ 67 , 68 , 69 , 70 ], and the NUDT5-selective inhibitor TH1457 blocks cell proliferation in breast cancer cells [ 71 ]. Given the interest in NUDT inhibition for the management of cancer patients, a greater understanding of the signaling pathways impinging on the activity of NUDT enzymes is required and may be facilitated by the interrogation of global phosphoproteomic and gene expression datasets ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 As such, the 5-year survival rate is roughly 30%, underscoring the urgent need for new therapies. 3 Proliferation, apoptosis, angiogenesis, tumor microenvironment, migration, and invasion are all factors that regulate the progression of malignant cancers, including osteosarcoma. 4 Therefore, the identification of mechanisms involved in osteosarcoma cell migration and invasion could lead to the development of novel therapeutic strategies used for the treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%